Do Financial Analysts Form Forecasts Rational? - Liu, Yang (2008)
Abstract Most prior studies test analyst's earnings forecast based on different assumptions of loss function. Under ordinary least squares (OLS) regression, prior studies find that financial analysts do not incorporate information rationally when they form their earnings forecasts. Some empirical studies argue that financial analysts tend to minimize the mean of forecasts errors, and then they actually face a linear loss function. Under least absolute deviation (LAD) regression, there is no strong evidence that analysts forecasts economically irrationality incorporate information when they form earnings forecasts. This paper test the rational expectation hypothesis on earnings forecast using under both OLS regression and LAD regression. The findings in this dissertation suggest that under the OLS regression, analysts forecasts are irrational that consistent with prior studies. However, the evidence of economically rational is found under the LAD regression tests.